THE ROLE OF THE NATIONAL VOCATIONAL TRAINING COUNCIL IN THE MANAGEMENT OF VOCATIONAL TRAINING - Ahmad Othman (2003)
In Malaysia, the responsibility to produce skilled manpower has rested heavily on the government. This can be seen by the increasing number of public training institutions in almost every five-year development plan. Malaysia has achieved much in producing skilled manpower through this effort. However, despite the significant increase in terms of training capacities and output over the years, Malaysia is still critically short of skilled manpower. In searching for the answer, this book tries to focus on the role of the National Vocational Training Council (NVTC).The study seeks to answer the following main question : How effective has the NVTC been in playing its role as an intermediary agency in the vocational training system of Malaysia? In carrying out this research, a number of different methods of data collection were employed, such as questionnaire, interview, documents review, and participant observation.